2013
DOI: 10.1021/cm401276y
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction Activity of Carbon-Supported La1–xCaxMn1–yFeyO3 Nanoparticles

Abstract: Carbon-supported La 1−x Ca x Mn 1−y Fe y O 3 nanoparticles were synthesized, and their oxygen reduction activities and electronic states were investigated. A reverse micelle method using KMnO 4 as a source of high valence state Mn successfully yielded carbon-supported La 1−x Ca x Mn 1−y Fe y O 3 nanoparticles even when calcined under a reducing atmosphere. The oxygen reduction activity of carbonsupported La 1−x Ca x Mn 1−y Fe y O 3 exceeded that of carbon-supported Pt nanoparticles when the Ca composition was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…b). Another study also supported the increased ORR activity for Mn ions over Fe ions in the La 0.4 Ca 0.6 Mn 1 − y Fe y O 3 oxides . These results indicate a synergistic electrocatalytic effect from the two transition‐metal ions.…”
Section: Perovskite Materials For Energy‐related Applicationsmentioning
confidence: 59%
“…b). Another study also supported the increased ORR activity for Mn ions over Fe ions in the La 0.4 Ca 0.6 Mn 1 − y Fe y O 3 oxides . These results indicate a synergistic electrocatalytic effect from the two transition‐metal ions.…”
Section: Perovskite Materials For Energy‐related Applicationsmentioning
confidence: 59%
“…Yuasa et al [131] [133]. Researchers [134,135] have also studied carbon-composited perovskite oxides derived from the substitution of both A and B sites as oxygen electrodes and have also found improved electrochemical properties.…”
Section: Composites Of Carbon and Perovskite Oxidesmentioning
confidence: 99%
“…As mentioned in Section 1, Yuasa et al reported the synthesis of perovskite‐type solid solution particles by the same RM methods with the carbon support at 873 K calcination, however, the size of them was large, about 20 nm. [ 31–34 ] The surface of TiO 2 , especially in an aqueous solution, has high density of hydroxyl groups compared to the carbon support. Therefore, it is speculated that the surface hydroxyl groups formed stronger interaction with the CFCO precursor, and such an interaction acts as the “linker” between the precursors and the TiO 2 surface to stably hold the small particles and to suppress the diffusion and aggregation of them during calcination at the high temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The RM method is one of the proven methods to synthesis of nanosized metal oxides. [ 31–34 ] Yuasa et al reported the syntheses of perovskite‐type LaMnO 3 [ 31,32 ] and La 1− x Ca x Mn 1− y Fe y O 3 [ 33,34 ] on a carbon support prepared by the RM method. The particle size of LaMnO 3 and La 1− x Ca x Mn 1− y Fe y O 3 synthesized by the RM method was smaller than those by the conventional methods, even though the particle sizes of the former ones were not several nanometer scales, i.e., ≈20 nm.…”
Section: Introductionmentioning
confidence: 99%